Development of novel functional foods using Himalayan honey having enhanced nutraceutical and nutritional potential - Ganie, Tariq Ahmad; Wani, Sajad Ahmad; Rather, Sajad Ahmad; Masoodi, Farooq Ahmad; Siddiqui, Shahida Anusha; Ibrahim, Salam A. (Frontiers in Sustainable Food Systems, 2022)
This study was carried out to conduct the geographical discrimination of various types of honey, and their utilization in development of novel functional foods where in honey could be substituted in place of white sugar. Honey based apple spread and marmalade products were developed and evaluated for quality analysis. The results showed higher water activity (aw) and moisture content in PR honey based apple spread and marmalade while, TSS was highest (p < 0.05) in MF honey based apple spread and marmalade. Hydroxymethylfurfural was found to be in the ranged of 6.77-7.05 (mg/kg) for honey based apple spread products and 3.09-3.46 (mg/kg) for honey based apple marmalade products. The lightness (L*) value was significantly highest in MF honey based apple spread and marmalades (p < 0.05). Redness (a*) and yellowness (b*) values were significantly highest in PR honey based apple spreads and marmalades and lowest in RSA honey based apple spread and marmalades. In general, all MF honey based apple spreads and marmalades has the highest score for overall acceptability in comparison to RSA and PR honey based apple spreads. The values of gel strength (Fe), rupture force (FR), energy of penetration (E) and adhesiveness (A) in the given spread products were in the range of 1.50–1.54 N, 1.70-1.73 N, 17.00-17.05 Ns and −1.11- −1.08 Ns, respectively. The values of gel strength (Fe), rupture force (FR), energy of penetration (E) and adhesiveness (A) in the investigated marmalade products were in the range of 1.65–1.69 N, 2.08-2.13 N, 16.05-16.10 Ns and −1.14- −1.10 Ns, respectively.